× Tritordeum martinii A. Pujadas (Poaceae) nothosp. nov. × Tritordeum martinii A. Pujadas (Poaceae) nothosp. nov. - Pujadas Salvá, Antonio J. (Acta Botanica Malacitana, 2016)
× Tritordeum martinii A. Pujadas (Poaceae) nothosp. nov. × Tritordeum martinii A. Pujadas (Poaceae) nothosp. nov.